ปัจจัยที่มีผลต่อระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้การ บริหารงานการเงินการคลังภาครัฐของหน่วยงานสนับสนุนภารกิจฝ่ายการเมือง - เณรวงค์, ธารินี (Journal of Business Administration The Association of Private Higher Education Institutions of Thailand, 2015)
การวิจัยเรื่องปัจจัยที่มีผลต่อระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้การบริหารงานการเงินการคลังภาครัฐของหน่วยงานสนับสนุนภารกิจฝ่ายการเมือง มีวัตถุประสงค์เพื่อ (1) ศึกษาความสัมพันธ์ระหว่างปัจจัยสภาพแวดล้อมการควบคุมของหน่วยงานสนับสนุนภารกิจฝ่ายการเมืองต่อระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้การบริหารงานการเงินการคลังภาครัฐ (2) เพื่อศึกษาและวิเคราะห์ระหว่างประเภทหน่วยงานสนับสนุนภารกิจฝ่ายการเมืองที่แตกต่างกัน ต่อปัจจัยสภาพแวดล้อมการควบคุม และระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้การบริหารงานการเงินการคลังภาครัฐ กลุ่มตัวอย่างที่ใช้ในการวิจัย คือผู้ปฏิบัติงานกองคลังของหน่วยงานสนับสนุนภารกิจฝ่ายการเมือง 3 หน่วยงาน ตั้งแต่ 3 ปีขึ้นไป จำนวน 208 คน เครื่องมือที่ใช้เป็นแบบสอบถามซึ่งได้รับการตอบกลับจ????ำนวน 192 คน คิดเป็นร้อยละ 92.31 และวิเคราะห์ ข้อมูลด้วยโปรแกรมสำเร็จรูปทางสถิติ สถิติที่ใช้ในการวิเคราะห์ข้อมูล คือการแจกแจงความถี่ (Frequency) ค่าร้อยละ(Percentage) ค่าสถิติ F-Test (ANOVA), ค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สัน (Pearson correlation) และวิเคราะห์การถดถอยพหุคูณ (Multiple Regression Analysis)ผลการวิจัย พบว่าปัจจัยด้านสภาพแวดล้อมการควบคุมของหน่วยงานสนับสนุนภารกิจฝ่ายการเมืองโดยรวมมีระดับการปฏิบัติที่ดี ซึ่งปัจจัยด้านปรัชญาและรูปแบบการทำงานของผู้บริหารมีระดับการปฏิบัติที่ดีสูงสุดรองลงมาด้านความซื่อสัตย์และจริยธรรมในการบริหารและการปฏิบัติงาน, ด้านนโยบายการบริหารและการพัฒนาด้านบุคลากร, ด้านการกำหนดอำนาจหน้าที่ความรับผิดชอบและด้านโครงสร้างของหน่วยงานตามลำดับ โดยพบว่าปัจจัยที่มีความสัมพันธ์และส่งผลต่อระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้ระบบการบริหารงานการเงินการคลังภาครัฐ คือ ปัจจัยด้านโครงสร้าของหน่วยงานและปัจจัยด้านนโยบายการบริหารและการพัฒนาด้านบุคลากรนอกจากนี้ยังพบว่าประเภทหน่วยงานสนับสนุนภารกิจฝ่ายการเมืองที่ต่างกัน จะมีปัจจัยด้านสภาพแวดล้อมการควบคุม และระดับการควบคุมภายในระบบสารสนเทศทางการบัญชีภายใต้ระบบการบริหารงาน การเงินการคลังภาครัฐแตกต่างกัน FACTORS AFFECTING THE LEVEL OF INTERNAL CONTROL OF THE ACCOUNTING INFORMATION SYSTEMS ON THE GOVERNMENT FISCAL MANAGEMENT INFORMATION SYSTEM IN THE POLITICAL SUPPORT MISSION AGENCIES The objective of the research, “Factors affecting the level of internal control of the accounting information systems on the Government Fiscal Management Information system in the political support mission agencies”, first to study on the relation between the control environments factors and the level of internal control of the accounting information systems; on the Government Fiscal Management Information system. Second, to study on the different levels of internal control related to the control environments factors and the level of internal control of the accounting information system; on the Government Fiscal Management Information system. The representative sample size was the officers of finance department in the political support mission agencies who have worked here more than 3 years, totaling 3 divisions, 208 people. The research tools were 192 questionnaires, with a return rate of 92.31 percent. Descriptive statistic, frequency and percentage, were used for data explanation while inferential statistic, F-Test (ANOVA), Pearson correlation, multiple regressions were used for hypothesis testing. The result of this research shown the overall practice on control environments factors of the political support mission agencies is good. The philosophy and operating style of management are in the highest level followed by the Integrity and ethics of management and operation, human resource policies and practices, assignment of authority and responsibility, and organizational structure respectively. Also the research has shown the important factor that affected to the level of internal control of the accounting information system were organization structure factor, human resource policies and practices factor. Other than that the different levels of the political support mission agencies will lead to the different factors of environments control and the level of internal control of the accounting information system; on the Government Fiscal Management Information system.